Heat transfer enhancement on tube surfaces with biphilic nanomorphology. (5th November 2020) - Zhu, Y.; Tso, C.Y.; Ho, T.C.; Leung, Michael K.H.; Yao, S.; Qiu, H.H.
Graphical abstract: Highlights: Heat transfer tubes with biphilic nanomorphology were fabricated; Heterogeneous condensation and droplet jumping were sustained on a biphilic tube; Convective heat transfer coefficient was enhanced on a biphilic tube; Condensation performance was improved on a biphilic heat exchanger. Abstract: The heat transfer performance of heat exchangers is extremely restricted due to the considerable thermal resistance of condensing droplets. By adopting the coalescence-induced droplet jumping phenomenon on a superhydrophobic coated surface, the condensing droplets can be spontaneously removed from the heat exchanger, and the heat transfer performance can be enhanced. However, under unfavorable conditions, the flooding effect, which restricts the droplet jumping rate and volume, occurs on heat exchangers and results in the degradation of heat transfer performance. In this study, novel heat transfer tubes with biphilic nanomorphology were fabricated and adopted to address the flooding issue and improve the heat transfer performance of heat exchangers. Through experiments we demonstrated that the droplet jumping effect could be sustained on a biphilic tube due to the formation of droplets in Cassie state during condensation. Because of the high droplet jumping and self-removal rate, the convective heat transfer coefficient was improved by 29% and 38% on a biphilic tube as compared with a typical copper tube and superhydrophobic tube, respectively. Besides, the condensation performance (i.e. water collection rate) on a biphilic heat exchanger prototype was also enhanced by 123% as compared with that on a copper heat exchanger prototype. This study not only enhances the condensation and convective heat transfer performance of heat exchangers by addressing the flooding issue, but also provides a practical strategy to improve the energy conversion efficiency of the thermal components with condensation effect in various thermal applications.